Serum miR-34a-5p and miR-199a-3p as new biomarkers of neonatal sepsis. - Omayma O Abdelaleem; Shereen Rashad Mohammed; Hassan S El Sayed; Sherin Khamis Hussein; Doaa Y Ali; Mostafa Y Abdelwahed; Sylvana N Gaber; Nada F Hemeda; Rehab G Abd El-Hmid (PLoS ONE)
Background Neonatal sepsis is a serious condition. Recent clinical studies have indicated that microRNAs (miRNAs) are key players in the pathogenesis of sepsis, which could be used as biomarkers for this condition. Patients and methods A total of 90 neonates with sepsis and 90 healthy neonates were enrolled in this study. qRT-PCR was performed to measure the expression levels of serum miR-34a-5p and miR-199a-3p. Results miR-34a-5p and miR-199a-3p serum levels were significantly reduced in neonates with sepsis compared with those in healthy neonates (P = 0.006 and P = 0.001, respectively). Significant correlations of miR-34a-5p and miR-199a-3p with each of TLC, RDW, RBS, and C-reactive protein (CRP) as well as SNAPII were observed, indicating their associations with the severity of neonatal sepsis. Conclusion miR-34a-5p and miR-199a-3p may be useful as novel biomarkers in neonatal sepsis and may provide a new direction for its treatment.